The state of the liver, reproductive and musculoskeletal systems in female rats with pro-longed exposure to α-cypermethrin - Makarenko, O. A.; Sidletskiy, O. S.; Khodakov, I. V. (Regulatory Mechanisms in Biosystems, 2024)
Pyrethroid insecticides are currently a widely used class of pesticides. It is therefore important to determine the mechanism of disorders in some mammalian systems due to prolonged exposure to these pesticides and to justify means to prevent poisoning complications. The study was conducted on 30 female rats aged 3 months for 120 days. Intoxication was modeled using α-cypermethrin at a dose of 10 mg/kg. The prevention of intoxication complications was carried out with an adaptogenic complex consisting of the flavonoid quercetin, vitamins C and D3, and minerals (Ca, Mn, Zn, Cu, Se, Mg) at a dose of 500 mg/kg. Assessment of intoxication and preventive efficacy of the adaptogen was performed by determining the duration of the estrous cycle, ovarian organ index, degree of atrophy of the alveolar process in the jaws, as well as density, content of mineral and organic components in the bones. Hepatotoxicity markers were determined in the blood serum, osteoresorption markers in the alveolar bone homogenate, inflammation indicators in the liver, and antioxidant system status in all tissues. Prolonged exposure to α-cypermethrin was associated with a prolongation of the estrous cycle due to a reduction in the diestrus stage and a decrease in the ovarian organ index along with a significant increase in blood estradiol levels. In intoxicated animals, the degree of atrophy of the alveolar process increased and the density of femurs and vertebrae decreased due to a decrease in the weight fraction of the mineral component in the bones. In the bone tissue of the alveolar process, an increase in the activity of elastase and markers of oxidative stress (an increase in the content of malondialdehyde and a decrease in catalase activity), as well as a compensatory increase in the alkaline phosphatase activity were found. In the rat liver, an increase in the acid phosphatase activity and the inhibition of antioxidant defense were observed. An increase in the elastase activity and a decrease in the catalase activity with an increase in the malondialdehyde content were found in the serum of the animals. The use of an adaptogen under conditions of α-cypermethrin intoxication contributed to the normalization of the estrous cycle, ovarian organ index and blood estradiol levels. In the tissue of the femur and vertebrae of rats, the treatment by the prophylactic complex led to an increase in bone density due to an increase in the content of the mineral component, and a decrease in the degree of atrophy of the jaws, in the tissue of which the activation of the enzymatic link of antioxidant defense and a decrease in the activity of destructive elastase too were found. The developed adaptogen prevented the development of oxidative stress and inflammation in the blood serum and liver in the animals. The results of the research indicate a negative effect of α-cypermethrin on the sexual function in female rats, on the state of bone tissue along with the hepatotoxic effect of the pesticide. The proposed agent for the prevention of α-cypermethrin intoxication effectively prevented endocrine disruption in the ovaries, bone destruction and inflammation in the liver.